2010
DOI: 10.1159/000284583
|View full text |Cite
|
Sign up to set email alerts
|

Leg Ulceration in Rheumatoid Arthritis – An Underreported Multicausal Complication with Considerable Morbidity: Analysis of Thirty-Six Patients and Review of the Literature

Abstract: Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease which may present with extra-articular symptoms, including cutaneous manifestations. Ulcerated rheumatoid nodules, necrotic vasculitic lesions and pyoderma gangrenosum are fairly characteristic and well-recognized causes of skin ulcers in RA. However, most RA patients develop leg ulcers due to other pathophysiological factors posing a diagnostic and therapeutic challenge and leading to considerable morbidity. Methods: A retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 65 publications
1
13
0
2
Order By: Relevance
“…Their findings suggest that local inflammatory response, as well as congestion of lymph channel, should be a necessary requirement for the development of this disease. Seitz et al [10] suggested that impaired morbidity and consecutive lymphedema are responsible for leg ulcerations in a considerable proportion of patients with RA, although it had been believed that vasculitis and pyoderma gangrenosum account for the majority of cases. Intralymphatic histiocytosis and leg ulcers thus seem to share some pathogenic factors in the sense that lymphostasis is an important precipitating factor and compression may be an effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest that local inflammatory response, as well as congestion of lymph channel, should be a necessary requirement for the development of this disease. Seitz et al [10] suggested that impaired morbidity and consecutive lymphedema are responsible for leg ulcerations in a considerable proportion of patients with RA, although it had been believed that vasculitis and pyoderma gangrenosum account for the majority of cases. Intralymphatic histiocytosis and leg ulcers thus seem to share some pathogenic factors in the sense that lymphostasis is an important precipitating factor and compression may be an effective treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology and localization of ulcerations, as well as Doppler ultrasonography, present the vital clues for accurate diagnosis, ensuring proper treatment. [19] About 2.7% of patients of a previous series had leg ulcers. [6] A relatively higher percentage (9.9%) of patients of the present series had such problem.…”
Section: Discussionmentioning
confidence: 99%
“…Three of the 16 patients with LE ulcers in this study (17) had biopsy proven vasculitis but it is unclear whether these results can be generalized as the sample size was small. Vasculitis was less common in LE ulcers in patients with RA in another institution-based retrospective study of hospitalized patients from a dermatology servicedivision (23). …”
Section: Discussionmentioning
confidence: 99%